Efficient nutrient recycling strategy through integrated nutrient management in hybrid napier within a coconut (Cocos nucifera)-based system - NIHAD, K; HARIS, A A; SUBRAMANIAN, P; MATHEW, JEENA; INDHUJA, S; NEENU, S; BHAT, RAVI; SHIL, SANDHIP (The Indian Journal of Agricultural Sciences, 2023)
The present field experiment was conducted to investigate the impact of various combinations of organic inputs on the growth of fodder grass in a coconut [Cocos nucifera (L.)]-based mixed farming during 2013–17 at ICAR-Central Plantation Crops Research Institute, Regional Station, Kayamkulam, Kerala and refined in farmer’s field during 2018–21. The experiment was conducted in randomized block design with seven treatments and three replications with one control [chemical fertilizer (CF) alone] and six organic recycling options with combination of a native strain of Azospirillum sp. [L8(3)] isolated from the coconut rhizosphere, [100% RDN through cow dung slurry (CDS), 100% RDN through coconut leaf vermicompost (CLVC), 100% RDN through CDS + CLVC (1:1), 100% RDN through CDS + CLVC (1:1) + Azospirillum sp., 75% RDN through CDS + CLVC (1:1) + Azospirillum sp. and 50% RDN through CDS + CLVC (1:1) + Azospirillum sp.]. Basal application of 15 tonnes of dried cow dung, 400 kg lime and 90:30:24 kg NPK/ha were supplied irrespective of the treatments. The plants supplied with 100% RDN through CF and CDS + CLVC + Azospirillum sp. recorded the higher yield during the first year, followed by a yield decline in subsequent years which may be due to the nitrogen-induced reduction in soil pH as evident from the soil analysis. The significantly higher fresh fodder yield (126.9 tonnes/ha/year), dry matter yield (22.7 tonnes/ha/year), neutral and acid detergent fibres, crude protein and plant nutrient uptake were recorded by plants supplied with 75% RDN through CDS + CLVC + Azospirillum sp. Technological refinement by adding additional lime (400 kg/ha) during second and third years resulted in 24.59% higher yield. This system of recycling resulted 50% reduction in external physical inputs during the first year and 90% reduction in subsequent two years.